The Course Development Plan: Macro‐Level Decisions and Micro‐Level Processes. Issue 173 (1st March 2016) - Franker, Karen; James, Dennis
Abstract : A key step in distance learning project management is the creation of a course development plan. The plan should account for decisions related to materials, curriculum, delivery methods, staffing, technology applications, resources, reporting lines, and project management—issues that may require administrator involvement and support, particularly for evolving distance learning programs.